Suitability of rangeland terrain for satellite remote sensing calibration - Teillet, P.M.; Ren, X.; Smith, A.M. (Canadian journal of remote sensing, 2010)
This paper reports on an investigation of the suitability of rangeland terrain as a terrestrial benchmark site for monitoring the radiometric performance of satellite sensors after launch. The test site considered is in Newell County rangeland in Alberta (NCRA). Seventy-two Landsat and 34 Satellite Pour l'Observation de la Terre (SPOT) images spanning 1985-2008 were used in the retrospective analysis. Coefficient of variation was used to assess the spatial uniformity and temporal stability of the surface radiometry. Mean top-of-atmosphere (TOA) reflectances were also examined. Image statistics were acquired for various window sizes within a region of 13 km × 13 km, the largest area common to almost all images of the NCRA region. Results are presented for a refined area of 3 km × 3 km and the most uniform 1 km × 1 km area within the refined area. In particular, the results indicate that the spatial radiometric uniformity of the 1 km × 1 km NCRA site has been consistently within 5% since 1985 but subject to considerable temporal variation within that 5%. Hence, the NCRA site is not deemed to be a strong candidate as a primary benchmark site for routine calibration monitoring purposes, although it could serve at times as a secondary site in the absence of or in addition to other possibilities.